Dispersion of the Vancomycin Resistance Genes vanA and vanC of Enterococcus Isolated from Nile Tilapia on Retail Sale: A Public Health Hazard - Osman, Kamelia M.; Ali, Mohamed N.; Radwan, Ismail; ElHofy, Fatma; Abed, Ahmed H.; Orabi, Ahmed; Fawzy, Nehal M. (Frontiers in Microbiology, 2016)
Although normally regarded harmless commensals, enterococci may cause a range of different infections in humans, including urinary tract infections, sepsis, and endocarditis. The acquisition of vancomycin resistance by enterococci (VRE) has seriously affected the treatment and infection control of these organisms. VRE are frequently resistant to all antibiotics that are effective treatment for vancomycin-susceptible enterococci, which leaves clinicians treating VRE infections with limited therapeutic options. With VRE emerging as a global threat to public health, we aimed to isolate, identify enterococci species from tilapia and their resistance to van-mediated glycopeptide (vanA and vanC) as well as the presence of enterococcal surface protein (esp) using conventional and molecular methods. The cultural, biochemical (Vitek 2 system) and PCR results revealed eight Enterococcus isolates from the 80 fish samples (10%) to be further identified as E. faecalis (6/8, 75%) and E gallinarum (2/8, 25%). Intraperitoneal injection of healthy Nile tilapia with the eight Enterococcus isolates caused significant morbidity (70%) within 3 days and 100% mortality at 6 days post injection with general signs of septicemia. All of the eight Enterococcus isolates were found to be resistant to tetracycline. The 6/6 E. faecalis isolates were susceptible for penicillin, nitrofurantoin, gentamicin, and streptomycin. On the other hand 5/6 were susceptible for ampicillin, vancomycin, chloramphenicol and ciprofloxacin. The two isolates of E. gallinarum were sensitive to rifampicin and ciprofloxacin and resistant to vancomycin, chloramphenicol and erythromycin. Molecular characterization proved that they all presented the prototypic vanC element. On the whole, one of the two vancomycin resistance gene was present in 3/8 of the enterococci isolates, while the esp virulence gene was present in 1/8 of the enterococci isolates. The results in this study emphasise the potential role that aquatic environments are correlated to proximity to anthropogenic activities in determining the antimicrobial resistance patterns of Enterococcus spp. recovered from fish in the river Nile in Giza, Elmounib, Egypt as a continuation of our larger study on the reservoirs of antibiotic resistance in the environment.